2022
DOI: 10.3390/nu14163326
|View full text |Cite
|
Sign up to set email alerts
|

Urbanization and Unfavorable Changes in Metabolic Profiles: A Prospective Cohort Study of Indonesian Young Adults

Abstract: The substantial increase in the prevalence of non-communicable diseases in Indonesia might be driven by rapid socio-economic development through urbanization. Here, we carried out a longitudinal 1-year follow-up study to evaluate the effect of urbanization, an important determinant of health, on metabolic profiles of young Indonesian adults. University freshmen/women in Jakarta, aged 16–25 years, who either had recently migrated from rural areas or originated from urban settings were studied. Anthropometry, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
(50 reference statements)
2
8
0
5
Order By: Relevance
“…The higher BMI, waist circumference, and obesity prevalence in urban compared to rural population observed in the current study, confirmed our previous findings ( Kurniawan et al, 2022 ). This present study also found these adiposity indices and obesity are positively correlated with diabetes in both populations, similar to what had been observed previously ( Bellou et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The higher BMI, waist circumference, and obesity prevalence in urban compared to rural population observed in the current study, confirmed our previous findings ( Kurniawan et al, 2022 ). This present study also found these adiposity indices and obesity are positively correlated with diabetes in both populations, similar to what had been observed previously ( Bellou et al, 2018 ).…”
Section: Discussionsupporting
confidence: 93%
“…This may result in obesity and consequent low-grade inflammatory state and insulin resistance, pathways leading to type 2 diabetes (T2D) ( Schuster, 2010 ). Our previous study in Indonesian young adults showed a higher prevalence of obesity in the urban compared to rural population ( Kurniawan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 92%
“…In a prospective, cohort study done in Indonesia, rural to urban migration, was associated with a disproportionately higher increase in BMI and leptin :adiponectin ratio compared to urban-to-urban migration. 35 Migration and urbanization may lead to unhealthy lifestyle modifications such as consumption of more processed food and physical inactivity, which ultimately lead to obesity and significantly impact one’s health. 24,25 More recently, another link between migration and obesity with its ensuing complication has been established.…”
Section: Discussionmentioning
confidence: 99%
“…In order to develop effective prevention programs, several cohort studies have been conducted to better understand the risk factors for MetS and examine MetS components [ 23 25 ], yet this prior research has limitations including relatively short follow-up times (one to four years) [ 26 ], variation in diagnostic criteria for MetS, or studies on populations of different ethnicities, which may affect generalisability to the Indonesian context [ 27 , 28 ]. Another study also explored MetS incidence using a similar six-year cohort, but did not rigorously select participants based on complete MetS component profiles and medication usage, which could introduce bias [ 29 ].…”
Section: Introductionmentioning
confidence: 99%